Triterpenoid profiling and functional characterization of the initial genes involved in isoprenoid biosynthesis in neem (Azadirachta indica) - Pandreka, Avinash; Dandekar, Devdutta S.; Haldar, Saikat; Uttara, Vairagkar; Vijayshree, Shinde G.; Mulani, Fayaj A.; Aarthy, Thiagarayaselvam; Thulasiram, Hirekodathakallu V. (BMC Plant Biology, 2015)
Background: Neem tree (Azadirachta indica) is one of the richest sources of skeletally diverse triterpenoids and they are well-known for their broad-spectrum pharmacological and insecticidal properties. However, the abundance of Neem triterpenoids varies among the tissues. Here, we delineate quantitative profiling of fifteen major triterpenoids across various tissues including developmental stages of kernel and pericarp, flower, leaf, stem and bark using UPLC-ESI (+)-HRMS based profiling. Transcriptome analysis was used to identify the initial genes involved in isoprenoid biosynthesis. Based on transcriptome analysis, two short-chain prenyltransferases and squalene synthase (AiSQS) were cloned and functionally characterized. Results: Quantitative profiling revealed differential abundance of both total and individual triterpenoid content across various tissues. RNA from tissues with high triterpenoid content (fruit, flower and leaf) were pooled to generate 79.08 million paired-end reads using Illumina GA.. platform. 41,140 transcripts were generated by d e novo assembly. Transcriptome annotation led to the identification of the putative genes involved in isoprenoid biosynthesis. Two short-chain prenyltransferases, geranyl diphosphate synthase (AiGDS) and farnesyl diphosphate synthase (AiFDS) and squalene synthase (AiSQS) were cloned and functionally characterized using transcriptome data. RT-PCR studies indicated five-fold and ten-fold higher relative expression level of AiSQS in fruits as compared to leaves and flowers, respectively. Conclusions: Triterpenoid profiling indicated that there is tissue specific variation in their abundance. The mature seed kernel and initial stages of pericarp were found to contain the highest amount of limonoids. Furthermore, a wide diversity of triterpenoids, especially C-seco triterpenoids were observed in kernel as compared to the other tissues. Pericarp, flower and leaf contained mainly ring-intact triterpenoids. The initial genes such as AiGDS, AiFDS and AiSQS involved in the isoprenoids biosynthesis have been functionally characterized. The expression levels of AiFDS and AiSQS were found to be in correlation with the total triterpenoid content in individual tissues.
Keywords: Azadirachta indica; Quantitative profiling; Transcriptome; Triterpenoids

Tracing the biosynthetic origin of limonoids and their functional groups through stable isotope labeling and inhibition in neem tree (Azadirachta indica) cell suspension - Aarthy, Thiagarayaselvam; Mulani, Fayaj A.; Pandreka, Avinash; Kumar, Ashish; Nandikol, Sharvani S.; Haldar, Saikat; Thulasiram, Hirekodathakallu V. (BMC Plant Biology, 2018)
Background Neem tree serves as a cornucopia for triterpenoids called limonoids that are of profound interest to humans due to their diverse biological activities. However, the biosynthetic pathway that plant employs for the production of limonoids remains unexplored for this wonder tree. Results Herein, we report the tracing of limonoid biosynthetic pathway through feeding experiments using C-13 isotopologues of glucose in neem cell suspension. Growth and development specific limonoid spectrum of neem seedling and time dependent limonoid biosynthetic characteristics of cell lines were established. Further to understand the role of mevalonic acid (MVA) and methylerythritol phosphate (MEP) pathways in limonoid biosynthesis, Ultra Performance Liquid Chromatography (UPLC)- tandem mass spectrometry based structure-fragment relationship developed for limonoids and their isotopologues have been utilized. Analyses of labeled limonoid extract lead to the identification of signature isoprenoid units involved in azadirachtin and other limonoid biosynthesis, which are found to be formed through mevalonate pathway. This was further confirmed by treatment of cell suspension with mevinolin, a specific inhibitor for MVA pathway, which resulted in drastic decrease in limonoid levels whereas their biosynthesis was unaffected with fosmidomycin mediated plastidial methylerythritol 4-phosphate (MEP) pathway inhibition. This was also conspicuous, as the expression level of genes encoding for the rate-limiting enzyme of MVA pathway, 3-hydroxy-3-methyl-glutaryl-coenzyme A reductase (HMGR) was comparatively higher to that of deoxyxylulose-phosphate synthase (DXS) of MEP pathway in different tissues and also in the in vitro grown cells. Thus, this study will give a comprehensive understanding of limonoid biosynthetic pathway with differential contribution of MVA and MEP pathways. Conclusions Limonoid biosynthesis of neem tree and cell lines have been unraveled through comparative quantification of limonoids with that of neem tree and through C-13 limonoid isotopologues analysis. The undifferentiated cell lines of neem suspension produced a spectrum of C-seco limonoids, similar to parental tissue, kernel. Azadirachtin, a C-seco limonoid is produced in young tender leaves of plant whereas in the hard mature leaves of tree, ring intact limonoid nimocinol accumulates in high level. Furthermore, mevalonate pathway exclusively contributes for isoprene units of limonoids as evidenced through stable isotope labeling and no complementation of MEP pathway was observed with mevalonate pathway dysfunction, using chemical inhibitors.